The Image of Climate Crisis in Media: A Conceptual Metaphor Analysis - Adam, Muhammad; Wahyuni, Wahyuni (Journal of Language and Literature, 2020)
The climate crisis is now become the world problem and a big environmental issue and has drawn attention of governments and media, the impact of the crisis can be reflected on how media describe the crisis using metaphors. The way media use the language metaphorically to describe the climate crisis is the focus of this study. Using conceptual metaphor analysis, researchers aim to identify the source domains of climate crisis metaphor which deliver the sense of urgency message related to climate crisis. The source of data is from ten news article from Guardian website which discuss the climate crisis. The result shows that various source domains are used to describe the climate crisis in metaphor: Climate Crisis is described as a War, as an Object in Motion, Directionality, a Vehicle, a Destination, a Political Ideology, a Wrestler, a Chemical Substance, and as a Natural Disaster. Although climate crisis is one of them described metaphorically as a destination where sooner or later without a drastic action, eventually the world will arrive there, but it implied an unwanted destination that should be avoided or else, turning back or stop towards the destination, and with the highest finding where climate crisis described as a war to fight and to combat, it shows that the climate crisis is a real threat to our world which everyone should take action to fight. This study shows that although the unintended entailments occurred, the source domain of war and destination deliver the sense of urgency of the climate crisis.Â